Nitrous oxide decomposition catalyst as well as preparation method and application thereof

By hydrothermal treatment of supported hydroxyl groups on the surface of Co3O4 spinel catalyst, the existing catalyst activity reduction and complex preparation problems are solved, and efficient N2O decomposition and anti-impact gas capabilities are achieved, and good industrial application prospects are provided.

CN119565611APending Publication Date: 2025-03-07SOUTHWEST JIAOTONG UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411832309.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing nitrous oxide decomposition catalysts have decreased activity in the presence of impurity gases and atmospheric pollutants, and the preparation process is complicated and the cost is high.

Method used

The hydroxyl group is supported on the surface of the Co3O4 spinel catalyst by hydrothermal treatment, which enhances the electron transfer process at the gas-solid interface of the catalyst surface, thereby improving the N2O decomposition activity of the catalyst and its ability to resist impurity gases.

Benefits of technology

It improves the N2O catalytic decomposition activity and stability of the catalyst, simplifies the preparation process, reduces production costs, and has no secondary pollution, and has good industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565611A_ABST
    Figure CN119565611A_ABST
Patent Text Reader

Abstract

The invention provides a nitrous oxide decomposition catalyst and a preparation method and application thereof, the catalyst is a Co3O4 spinel catalyst, hydroxyl (-OH) is loaded on the surface of Co3O4 through hydrothermal treatment, the electron transfer process of a gas-solid interface on the surface of the catalyst is enhanced, and therefore the N2O decomposition performance is improved. The catalyst has high reaction activity, excellent stability and impurity gas tolerance, is simple in preparation process, low in cost and free of secondary pollution, and has a good industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of air pollution control, and in particular to a nitrous oxide decomposition catalyst and a preparation method and application thereof. Background Art

[0002] Nitrous oxide (N2O) is a potent greenhouse gas with a global warming potential of approximately 310 times that of carbon dioxide. In recent years, N2O emissions from industrial sources, especially in the production of nitric acid and adipic acid, have been steadily increasing. Therefore, there is an urgent need to explore effective methods to reduce N2O emissions. Direct catalytic decomposition of N2O has the characteristics of good cost-effectiveness, high decomposition efficiency, and no by-products. However, affected by actual working conditions, common transition metal oxide catalysts are easily poisoned and deactivated due to competitive adsorption of impurity gas molecules such as NO, O2, and water vapor, and their activity is reduced due to the influence of other atmospheric pollutants such as NH3. In water pollution treatment, hydroxyl radicals usually act as key active oxygen to promote the electron transfer process and significantly improve the removal efficiency of pollutants. However, in the research of N2O decomposition catalysts and even catalysts for atmospheric pollutants, the positive effect of hydroxyl on catalysts has not been reported.

[0003] Transition metal oxides with spinel structures are usually expressed as AB2O4, where A represents a divalent cation at a tetrahedral position and B represents a trivalent cation at an octahedral position. This special structure enhances the redox properties of divalent and trivalent cations and promotes charge transfer during N2O decomposition. Extensive studies have shown that Co3O4 spinel catalysts have good N2O decomposition activity and can maintain activity even in the presence of impurities such as oxygen and water vapor.However, in the prior art (Reference 1: Gong, Y.; Liu, Z.; Li, Z.; Liu, C.; Yan, N.; Ma, L. Boosting N2Odecomposition by fabricating the Cs-O-Co structure over Co3O4 with single-layer atoms of Cs. Environ. Sci. Technol. 2024, 58, 906-914; Reference 2: Nowakowski, L.; Hudy, C.; Zasada, F.; Grybos, J.; Piskorz, W.; Wach, A.;Kayser, Y.; Szlachetko, J.; Sojka, Z. N2O decomposition on singly and doubly(K and Li)-doped Co3O4 nanocubes horizontal line establishing key factors governing redox behavior of catalysts. J. Am. Chem. Soc. 2024, 146, 24450-24466; Reference 3: Abu-Zied, BM; Soliman, SA; Asiri, AM Role ofrubidium promotion on the nitrous oxide decomposition activity ofnanocrystalline Co3O4-CeO2 catalyst. Appl. Surf. Sci. 2019, 479, 148-157; Reference 4: Hu, X.; Wang, Y.; Wu, R.; Zhao, L.; Wei, X.; Zhao, Y. Effects ofzirconia crystal phases on the catalytic decomposition of N2O over Co3O4 / ZrO2catalysts. Appl. Surf. Sci. 2020, 514, 145892.), in order to further improve the catalytic activity of Co3O4 spinel catalyst, Co3O4 is usually compounded with other elements, which makes the preparation process cumbersome and increases the production cost of the catalyst. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a nitrous oxide decomposition catalyst and a preparation method and application thereof. The catalyst adopts hydrothermal treatment to load hydroxyl groups on the traditional Co3O4 spinel catalyst, thereby enhancing the electron transfer process at the gas-solid interface on the catalyst surface, thereby improving the catalyst's N2O catalytic decomposition activity and resistance to impurity gases, ensuring the stability of the catalyst, and having the advantages of simple preparation process, low cost, no secondary pollution, etc., and can be used for tail gas treatment in the production of nitric acid and adipic acid, and has good industrial application prospects.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] A nitrous oxide decomposition catalyst is a Co3O4 spinel catalyst and a hydroxyl group (-OH) is loaded on the surface of the Co3O4.

[0007] Furthermore, the hydroxyl groups were loaded via a hydrothermal method.

[0008] Furthermore, the particle size of the Co3O4 is 40-60 nm.

[0009] Furthermore, XPS detection showed that the hydroxyl oxygen content on the catalyst surface accounted for 4.9~11.8% of the surface oxygen content. Specifically, this content refers to the number of oxygen atoms, that is, moles / mass.

[0010] A method for preparing a nitrous oxide decomposition catalyst comprises the following steps:

[0011] Step A, prepare an appropriate amount of Co(NO3)2·6H2O, add an appropriate amount of ultrapure water and stir evenly with magnetic force;

[0012] Step B: After the stirring reaches stability, add an appropriate amount of 1 mol / L NaOH solution and continue stirring for 60 min;

[0013] Step C, transferring the mixed solution obtained in step B to a stainless steel hydrothermal reactor with a Teflon liner, and placing it in a blast oven preheated to 150° C. to keep warm;

[0014] Step D: Cool the mixed solution obtained in step C to room temperature, wash it with deionized water to obtain a solid powder; place the solid powder in an oven for drying, and calcine it in a muffle furnace to obtain a Co3O4 catalyst.

[0015] Specifically, the insulation time in step C is 4 to 16 h, preferably 8 h.

[0016] Specifically, in step D, the drying temperature is 80-120° C., the time is 4-16 h, the calcination temperature is 350-550° C., the time is 2-8 h, and the heating rate is 2-20° C. / min.

[0017] Through hydrothermal treatment, hydroxyl groups can be loaded on the surface of the Co3O4 catalyst, and the electron transfer process at the gas-solid interface on the catalyst surface can be enhanced, thereby improving the catalytic decomposition effect of nitrous oxide of the catalyst. Generally, as the hydrothermal time increases, more hydroxyl groups will be formed on the catalyst surface, but hydroxyl overload will lead to unstable hydroxyl groups and decreased loading. In the preparation process of the catalyst of the present invention, a catalyst with a high hydroxyl loading is obtained by ensuring a specific hydrothermal treatment duration, thereby ensuring a high nitrous oxide decomposition rate of the catalyst.

[0018] Beneficial effects of the present invention: The nitrous oxide decomposition catalyst provided by the present invention uses cobalt tetraoxide spinel as a catalyst component, and loads hydroxyl groups (-OH) on the catalyst surface through hydrothermal treatment. The surface hydroxyl groups enhance the electron transfer process at the gas-solid interface on the catalyst surface, which plays an important role in promoting the catalyst activity. The surface hydroxyl content can reach the maximum value under the hydrothermal time of 8 hours, and the nitrous oxide decomposition performance of the catalyst is optimal. The above catalyst also has good resistance to impurity gases and stability. The catalyst provided by the present invention has a simple preparation process, low raw material price, low production cost, and no secondary pollution, and has good industrial application prospects in the field of tail gas treatment in nitric acid production and adipic acid production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Attached Figure 1 : XRD test results of the Co3O4 catalysts prepared in Examples 1 to 3 and the Co3O4 catalysts in the comparative example.

[0020] Attached Figure 2 : Infrared spectra of the Co3O4 catalysts prepared in Examples 1 to 3 and the Co3O4 catalysts in the comparative example.

[0021] Attached Figure 3 : N2O catalytic activity of the Co3O4 catalysts prepared in Examples 1 to 3 and the Co3O4 catalysts in the comparative example.

[0022] Attached Figure 4 : Normalized reaction rate of N2O catalytic decomposition of Co3O4 catalysts prepared in Examples 1 to 3 and the Co3O4 catalysts in the comparative example at 450°C.

[0023] Attached Figure 5 : Correlation between the surface hydroxyl content and the normalized reaction rate of the Co3O4 catalysts prepared in Examples 1 to 3 and the Co3O4 catalysts in the comparative example.

[0024] Attached Figure 6 : Comparison between the Co3O4-8 catalyst prepared in Example 2 and the typical Co-based catalyst T50.

[0025] Attached Figure 7 : Experimental results of the resistance of the Co3O4-8 catalyst prepared in Example 2 to impurity gases.

[0026] Attached Figure 8 : Stability test results of the Co3O4-8 catalyst prepared in Example 2 at 350°C. DETAILED DESCRIPTION

[0027] The technical solutions in the present invention are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the protection scope of the present invention.

[0028] The nitrous oxide decomposition catalyst of the present invention and its preparation method and application are described in detail below.

[0029] A nitrous oxide decomposition catalyst, which is a Co3O4 spinel catalyst and has hydroxyl groups (-OH) loaded on the surface of the Co3O4, and the surface hydroxyl groups play an important role in promoting activity. The particle size of the Co3O4 is 40-60 nm, and through XPS detection, the hydroxyl oxygen content on the catalyst surface accounts for 4.9-11.8% of the surface oxygen content, specifically, the content refers to the number of oxygen atoms, that is, moles / mass.

[0030] Specifically, the preparation method of the nitrous oxide decomposition catalyst may include the following steps:

[0031] Step A, prepare an appropriate amount of Co(NO3)2·6H2O, add an appropriate amount of ultrapure water and stir evenly with magnetic force;

[0032] Step B: After the stirring reaches stability, add an appropriate amount of 1 mol / L NaOH solution and continue stirring for 60 min;

[0033] Step C, transferring the mixed solution obtained in step B to a stainless steel hydrothermal reactor with a Teflon liner, and placing it in a blast oven preheated to 150° C. to keep warm;

[0034] Step D: Cool the mixed solution obtained in step C to room temperature, wash it with deionized water to obtain a solid powder; place the solid powder in an oven for drying, and calcine it in a muffle furnace to obtain a Co3O4 catalyst.

[0035] Furthermore, the nitrous oxide decomposition catalyst provided by the present invention can be used in the field of tail gas treatment in the production of nitric acid and adipic acid. The hydroxyl group is loaded on the traditional Co3O4 spinel catalyst, which enhances the electron transfer process at the gas-solid interface on the catalyst surface, improves the catalytic decomposition activity and resistance to impurity gases of the catalyst, and the catalyst has good stability. The above catalyst also has the advantages of simple preparation process, low cost, no secondary pollution, etc., and has good industrial application prospects.

[0036] In order to more clearly demonstrate the technical solution and technical effects provided by the present invention, the surface-loaded hydroxyl group-containing nitrous oxide decomposition catalyst and its preparation method and application in the present invention are described in detail below with reference to specific embodiments.

[0037] Example 1

[0038] A nitrous oxide decomposition catalyst, the preparation method of which may include the following steps:

[0039] Step A, weigh 11.64 g Co(NO3)2·6H2O, add 10 mL ultrapure water and stir magnetically;

[0040] Step B: After the stirring reaches a stable state, add 10 ml of 1 mol / L NaOH solution and continue stirring for 60 min;

[0041] Step C, transferring the mixed solution obtained in step B to a stainless steel hydrothermal reactor with a Teflon liner, and placing it in a forced air oven preheated to 150° C. for 4 h;

[0042] Step D: After the mixed solution obtained in step C is cooled to room temperature, it is washed with deionized water to obtain a solid powder. The solid powder is placed in an oven to dry at a drying temperature of 100°C for 12 hours; then placed in a muffle furnace for calcination at a calcination temperature of 500°C for 2 hours at a heating rate of 2°C / min to obtain a Co3O4 catalyst, which is recorded as Co3O4-4.

[0043] Embodiment 2-3

[0044] The same catalyst preparation method as in Example 1 was adopted, only the hydrothermal treatment time in step C was adjusted, and Co3O4 catalysts with hydrothermal times of 8 h and 16 h were prepared, which were respectively recorded as Co3O4-8 and Co3O4-16.

[0045] Comparative Example

[0046] The same catalyst preparation method as in Example 1 was adopted, except that the hydrothermal treatment in step C was not performed, and the prepared catalyst was recorded as Co3O4-0.

[0047] The specific surface areas of the Co3O4-4, Co3O4-8, Co3O4-16 catalysts prepared in Examples 1 to 3 and the Co3O4-0 catalyst prepared in the comparative example were tested, and the results are shown in the following table: sample <![CDATA[S BET (m 2 g -1 )]]> <![CDATA[Co3O4-0]]> 14.6 <![CDATA[Co3O4-4]]> 15.1 <![CDATA[Co3O4-8]]> 11.1 <![CDATA[Co3O4-16]]> 7.4

[0048] It can be seen that hydrothermal treatment did not increase the BET specific surface area of ​​Co3O4 catalyst.

[0049] XRD tests were performed on the Co3O4-4, Co3O4-8, Co3O4-16 catalysts prepared in Examples 1 to 3 and the Co3O4-0 catalyst prepared in the comparative example. The results are shown in the attached Figure 1 It can be seen that with the increase of hydrothermal time, the peak position of the catalyst has no obvious change, that is, the crystal structure of the catalyst has not changed, and it is Co3O4 spinel (PDF#42-1467).

[0050] The Co3O4-4, Co3O4-8, Co3O4-16 catalysts prepared in Examples 1 to 3 of the present invention and the Co3O4-0 catalyst prepared in the comparative example were subjected to infrared spectroscopy testing. The results are shown in the attached Figure 2 All hydrothermally treated samples exhibited stronger vibration peaks than Co3O4-0, indicating successful loading of hydroxyl groups on the catalyst surface. Co3O4-8 exhibited the strongest vibration peak, indicating that it had the highest surface hydroxyl content.

[0051] The Co3O4-4, Co3O4-8, Co3O4-16 catalysts prepared in Examples 1 to 3 of the present invention and the Co3O4-0 catalyst prepared in the comparative example were used to conduct experiments on a N2O catalytic test device, and the experimental conditions were as follows:

[0052] The catalyst was pressed and granulated to a size of 40-60 mesh. 200 mg of catalyst was filled on the top of the quartz sand core of the fixed bed reactor, and then a small amount of quartz wool was filled on the top of the catalyst particles. The N2O concentration in the reaction gas component was adjusted to 1000 ppm, and the total gas flow rate was maintained at 200 mL min −1 , gas hourly space velocity (GHSV) is 60000 mL g −1 ·h −1 Set the temperature control program, where the heating rate is 5 ℃·min −1 , keep the temperature at each target temperature for 0.5 h, and detect the composition of the outlet exhaust gas in real time. N2O conversion rate (X N2O ) is calculated as follows:

[0053] Wherein, Cinput (ppm) and Cout (ppm) are the N2O concentrations in the input and output reactors, respectively.

[0054] In order to further study the intrinsic reaction activity of the catalyst, the normalized reaction rate of the catalyst at 450 °C was calculated, and the calculation formula is as follows:

[0055] In the formula, F 输入 (mL min -1 ) represents the inlet gas flow rate, W 催化剂 (g) represents the mass of the catalyst, S BET (m 2 g -1 ) represents the BET specific surface area of ​​the catalyst.

[0056] The N2O catalytic activity test results and normalized reaction rate calculation results of the Co3O4-4, Co3O4-8, Co3O4-16 catalysts prepared in Examples 1 to 3 and the Co3O4-0 catalyst prepared in the comparative example are shown in the attached Figure 3-4 It can be seen that with the extension of hydrothermal treatment time, the activity of Co3O4 catalyst first increases and then decreases. The Co3O4-8 catalyst hydrothermally treated for 8 h has the most hydroxyl groups on its surface, and its N2O conversion rate and N2O reaction rate are the highest, indicating that it has the best N2O catalytic decomposition activity. Further analysis of the correlation between the catalyst surface hydroxyl content and the normalized reaction rate is shown in the attached Figure 5 , it can be seen that the trend of hydroxyl content is significantly correlated with the reaction rate, and higher hydroxyl content corresponds to better catalytic performance.

[0057] The Co3O4-8 catalyst with the best catalytic decomposition activity was selected to compare T50 (the temperature at which the conversion rate is 50%) with the Co-based catalyst mentioned in the background technology. The results are shown in the attached Figure 6 It can be seen that the Co3O4-8 catalyst in the present invention has not been modified by other elements, but it also shows high activity under high space velocity conditions.

[0058] The Co3O4-8 catalyst with the best catalytic activity was selected for the impurity gas resistance test and stability test. The conditions of the impurity gas resistance test were as follows: 200 mg, 40-60 mesh catalyst, gas flow rate 200 ml / min, 1000 ppmN2O, 2% O2 (when used), 200 ppm NO (when used), 200 ppm NH3 (when used) and 3% H2O (when used), N2 was used as the balance gas, and the corresponding gas hourly space velocity (GHSV) was 60000 mL·g -1 ·h -1The gaseous H2O was introduced by N2 in a water bath at 25°C. The stability test experimental conditions were as follows: 200 mg, 40-60 mesh catalyst, gas flow rate 200 ml / min, reaction temperature 350°C, 1000 ppm N2O, N2 as the balance gas, and the corresponding gas hourly space velocity (GHSV) was 60000 mL·g -1 ·h -1 The experimental results are shown in the attached Figure 7 , 8 .

[0059] It can be seen that the Co3O4-8 catalyst hydrothermally treated for 8 hours has good resistance to impurity gases and good high-temperature stability.

[0060] Density functional theory analysis (DFT simulation analysis) was further used. DFT simulation analysis showed that in the N2O decomposition reaction cycle, the rate-limiting step is the breaking of the NO bond. The introduction of -OH promotes the electron transfer from Co to N2O, helps the breaking of the NO bond, and reduces the energy barrier of the reaction cycle. Therefore, even after hydrothermal treatment, the specific surface area of ​​the catalyst is reduced, but the N2O decomposition activity is still improved.

[0061] In summary, the -OH group introduced by the hydrothermal treatment in the present invention enhances the N2O adsorption of the Co3O4 catalyst and promotes the electron transfer from the Co3O4 surface to the N2O molecule, thereby promoting the breaking of the NO bond and improving the N2O decomposition activity of the catalyst. The catalyst in the present invention not only has good catalytic activity and stable performance, but also has a simple preparation process, low cost, no secondary pollution, and has good application prospects.

[0062] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A nitrous oxide decomposition catalyst, which is a Co3O4 spinel catalyst and a hydroxyl group (-OH) is loaded on the surface of the Co3O4.

2. A nitrous oxide decomposition catalyst as claimed in claim 1, further, the hydroxyl group is supported by a hydrothermal method.

3. A nitrous oxide decomposition catalyst as claimed in claim 1, further, the particle size of the Co3O4 is 40-60nm.

4. A nitrous oxide decomposition catalyst as claimed in claim 1, further, through XPS detection, the hydroxyl oxygen content on the catalyst surface accounts for 4.9-11.8% of the surface oxygen content.

5. A method for preparing a nitrous oxide decomposition catalyst as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: Step A, prepare an appropriate amount of Co(NO3)2·6H2O, add an appropriate amount of ultrapure water and stir magnetically; Step B: After the stirring reaches stability, add an appropriate amount of 1 mol / L NaOH solution and continue stirring for 60 min; Step C, transferring the mixed solution obtained in step B to a stainless steel hydrothermal reactor with a Teflon liner, and placing it in a blast oven preheated to 150° C. to keep warm; Step D: Cool the mixed solution obtained in step C to room temperature, wash it with deionized water to obtain a solid powder; place the solid powder in an oven for drying, and calcine it in a muffle furnace to obtain a Co3O4 catalyst.

6. A preparation method according to claim 5, characterized in that: In step C, the insulation time is 4 to 16 h.

7. A preparation method according to claim 6, characterized in that: In step C, the holding time is 8 h.

8. A preparation method according to claim 5, characterized in that: In step D, the drying temperature is 80-120° C., the time is 4-16 h, the calcination temperature is 350-550° C., the time is 2-8 h, and the heating rate is 2-20° C. / min.

9. Use of the nitrous oxide decomposition catalyst as claimed in any one of claims 1 to 4 for treating tail gas from nitric acid production and adipic acid production.